Age and Emotion Affect How We Look at a Face: Visual Scan Patterns Differ for Own-Age versus Other-Age Emotional Faces - Ebner, Natalie C. (2011)
We investigated how age of faces and emotion expressed in faces affect young (n = 30) and older (n = 20) adults’ visual inspection while viewing faces and judging their expressions. Overall, expression identification was better for young than older faces, suggesting that interpreting expressions in young faces is easier than in older faces, even for older participants. Moreover, there were age-group differences in misattributions of expressions, in that young participants were more likely to label disgusted faces as angry, whereas older adults were more likely to label angry faces as disgusted. In addition to effects of emotion expressed in faces, age of faces affected visual inspection of faces: Both young and older participants spent more time looking at own-age than other-age faces, with longer looking at own-age faces predicting better own-age expression identification. Thus, cues used in expression identification may shift as a function of emotion and age of faces, in interaction with age of participants.